Pengembangan Game Molemash di Android Menggunakan Metode Rapid Application Development - Agus Cahyo Nugroho (Indonesian Society of Applied Science, 2020)
As we know the game is one of the interesting applications found in gadgets. Many people who play games use their gadgets. The fans of this game come from various age segments. Although the majority is dominated by children and adolescents. Molemash is one of the popular games since time immemorial. This Molemash game is played by touching certain characters that appear on the gadget's screen. The aim of developing this Molemash game is as a media to entertain children during the Covid-19 pandemic. Another goal is to introduce programming to today's parents. The development method used is Rapid Application Development (RAD). One application that supports the RAD method is MIT App Inventor 2. MIT App Inventor 2 is one of the tools that supports the RAD method because it implements block programming so that it allows efficiency in terms of program lines that must be written. One block at MIT App Inventor 2 represents dozens or even hundreds of program lines. Users only need to arrange the blocks according to the desired logic flow. Therefore MIT App Inventor 2 is suitable for rapid software development. The result of developing this Molemash game is that children get alternative entertainment during the Covid-19 pandemic. Whereas in terms of parents get new knowledge related to game development on Android.